Efektivitas Alih Baring Tiap 2 Jam Terhadap Pencegahan Ulkus Dekubitus pada Pasien Pasca Stroke dengan Tirah Baring Lama di Bangsal Saraf RSUD Arifin Achmad Pekanbaru - Bevi Dewi Citra; Hermes C. Sitompul; Tuti Restuastuti (Fakultas Kedokteran Universitas Riau, 2010)
Neurological deficits on stroke patients can caused immobility. Decubitus ulcer is one of immobilty’s complication.Two hours repositioning is one of medical rehabilitation programs in decubitus prevention. The aim of this study is todescribe effectiveness of two hours repositioning to prevent decubitus ulcer, especially on post-stroke patients. Thisstudy was a preventive intervention study with cross-sectional approach. Sample consists of 32 patients. Group Iconsists of 16 patients with repositioning intervention. On the otherhand, group II consists of 16 patients withoutrepositioning intervention. Then, this two groups were compared and were looked for the effectiveness. from thisstudy, we knew that prevalence of decubitus ulcer on post-stroke patients are 19.4% with the effectiveness of two hoursrepositioning is 87.5%. There was significant difference between these two groups to prevent decubitus. it occurred ongeriatric patients with percentage of 75%. Its Proportion for female: male are 2:1. It is commonly occurred on firstweek hospitalization, especially grade 2 (33.3%). It is mostly located on sacrum (100%).